Context and target recollection for words and pictures in young adults with developmental dyslexia - Obidziński, Michał; Nieznański, Marek (Frontiers in Psychology, 2022)
Introduction The specificity of memory functioning in developmental dyslexia is well known and intensively studied. However, most research has been devoted to working memory, and many uncertain issues about episodic memory remain practically unexplored. Moreover, most studies have investigated memory in children and adolescents—much less research has been conducted on adults. The presented study explored the specificity of context and target memory functioning for verbal and nonverbal stimuli in young adults with developmental dyslexia. Methods The dual recollection theory, which distinguishes context recollection, target recollection, and familiarity as the processes underlying memory performance in the conjoint recognition paradigm, was adopted as the theoretical basis for the analysis of memory processes. The employed measurement model, a multinomial processing tree model, allowed us to assess the individual contributions of the basic memory processes to memory task performance. Results The research sample consisted of 82 young adults (41 with diagnosed dyslexia). The results showed significant differences in both verbal and nonverbal memory and context and target recollection between the dyslexic and the typically developing groups. These differences are not global; they only involve specific memory processes. Discussion In line with previous studies using multinomial modeling, this shows that memory functioning in dyslexia cannot be characterized as a simple impairment but is a much more complex phenomenon that includes compensatory mechanisms. Implications of the findings and possible limitations are discussed, pointing to the need for further investigation of the relationship between context memory functioning and developmental dyslexia, taking into account the type of material being processed.